Localizing Shakespeare as folk performance - Abad, Ricardo G.; Santamaria, MCM (2020)
Based on Romeo and Juliet and a 1901 awit adaption of Shakespeare's play, the theater production Sinang Dalisay deploys, as its movement motif, the igal, a dance tradition of the Sama Bajau of the southern Philippines. The use of the motif influences other elements in the production, specifically, the music, the decision to set the play in a Muslim community, the set and costume designs, and the change of the characters' names into more local appellations. The localized production adopts a collaborative intercultural approach to theater-making, with Muslim and Christian artists working together to teach the dance to performers, help reconfigure the dance for the contemporary stage, and align that reconfiguration with community practice. This paper reviews the production, assesses its reception on etic and emic levels, and contextualizes the project in terms of Muslim-Christian relations in the Philippines. It finds that the task of localizing Shakespeare as folk dance must contend, onstage, with issues of cultural and political representation and, most importantly, offstage, with ethical issues that underlie collaborative intercultural theater. The offstage component makes the production a vehicle to advance mutual solidarity between Muslims and Christians.
Keywords: Intercultural theater; Theater